Transient Headache and Neurological Deficits with cerebrospinal fluid Lymphocytosis (HaNDL-syndrome) with an acute confusional state and papilledema in a 10-year old girl: a case report - Vermaning, Sietske; Jansen, Anna; Vanderhasselt, Tim; Régal, Luc; Wassenberg, Tessa (Belgian Journal of Paediatrics, 2023)
The syndrome of transient Headache and Neurological Deficits with cerebrospinal fluid Lymphocytosis (HaNDL-syndrome) is a rare entity of unknown aetiology. We present a 10-year-old girl, with three episodes of HaNDL-syndrome, each characterized by slightly different neurological symptoms and signs. As HaNDL is a rare syndrome, a standardized therapeutic strategy has not been established. Treatment mainly consists of supportive therapy and in case of papilledema acetazolamide must be considered. We suspect that the diagnosis is often missed or mistaken for other neurological disorders.